2020
DOI: 10.1002/alz.12162
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected awakenings in severe dementia from case reports to laboratory

Abstract: Objective: Case report notions of unexpected memory retrieval in patients with severe dementia near to death are starting to alter the central "irreversible" paradigm of dementia and locate dementia as a problem of memory retrieval, not consolidation. We suggest that the most likely central tenet of this paradoxical memory retrieval is the fluctuation of neuromodulators projecting from the brain stem to the medial prefrontal cortex and the hippocampus. The neuromodulation-centric explanation of this phenomenon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 109 publications
(214 reference statements)
0
7
0
Order By: Relevance
“…Following initial publications that highlighted new fields of research in dementia diseases (Eldadah et al, 2019;Mashour et al, 2019), six research projects with a funding volume of about two million dollars have lately been launched by the National Institute of Health (NIH, 2020). Furthermore, several recent publications have examined lucid episodes in dementias from different angles (Bostanciklioğlu, 2021;Gilmore-Bykovskyi et al, 2021;Morris & Bulman, 2020Ney et al, 2021;Peterson et al, 2021). However, there seems to exist uncertainty regarding the precise understanding of the concept of terminal lucidity.…”
Section: Overview Of Some Riddles Of the Mindmentioning
confidence: 99%
See 1 more Smart Citation
“…Following initial publications that highlighted new fields of research in dementia diseases (Eldadah et al, 2019;Mashour et al, 2019), six research projects with a funding volume of about two million dollars have lately been launched by the National Institute of Health (NIH, 2020). Furthermore, several recent publications have examined lucid episodes in dementias from different angles (Bostanciklioğlu, 2021;Gilmore-Bykovskyi et al, 2021;Morris & Bulman, 2020Ney et al, 2021;Peterson et al, 2021). However, there seems to exist uncertainty regarding the precise understanding of the concept of terminal lucidity.…”
Section: Overview Of Some Riddles Of the Mindmentioning
confidence: 99%
“…In such cases, both terms fit and one could even speak of "paradoxical terminal lucidity." Mehmet Bostanciklioğlu (2021) has already used this formulation, but only casually and without explaining the rationale behind using these terms in this manner. In fact, he used the terms terminal lucidity and paradoxical lucidity largely interchangeably in his article, but seemed to regard terminal lucidity as a kind of umbrella term with paradoxical lucidity being a property of terminal lucidity.…”
Section: The Distinction Between Terminal and Paradoxical Luciditymentioning
confidence: 99%
“…He also spoke of "paradoxical terminal lucidity" on two occasions. 1 Contrastingly, the second authors suggested that terminal lucidity should be regarded as an instance of paradoxical lucidity. 2 While I thoroughly appreciate that the subjects of terminal and paradoxical lucidity have found their way into professional medical research venues, a clarification regarding the precise meaning of these terms seems apt to avoid nurturing further misunderstandings.…”
Section: E T T E R Terminal Lucidity Versus Paradoxical Lucidity: a T...mentioning
confidence: 99%
“…While not exclusive to AD, these episodes of spontaneous, meaningful communication and connectedness in individuals presumed to have lost the capacity for coherent verbal and behavioral interaction challenge over a century of assumptions (Mashour et al, 2019). These cases of memory retrieval, often near death, bring into question the central "irreversible" paradigm of dementia, thereby supporting the construct of dementia as a problem with memory retrieval rather than memory consolidation (Bostanciklioglu, 2021).…”
Section: Memory and Awareness In Persons With Alzheimer's Diseasementioning
confidence: 99%
“…The mechanisms of the network level return of PL are currently under exploration, hypothesizing the fluctuation of brainstem neuromodulator circuitry projecting to the medial prefrontal cortex and hippocampus, in addition to corticotropin-releasing peptides that may increase mental clarity and excitability of this circuitry ( Mashour et al, 2019 ; Bostanciklioğlu, 2021 ). A recent study of 124 dementia patients who exhibited pre-death PL suggested the existence of a reversible and functional aspect of pathophysiology of dementia, even in severe cases ( Batthyány and Greyson, 2020 ).…”
Section: Consciousness In Alzheimer’s Disease: Preserved Cognitions Emotions and Subjective Experiencementioning
confidence: 99%